Melanoma: tumor microenvironment and new treatments - Giavina-Bianchi,Mara Huffenbaecher (2017)
Abstract: In the recent past years, many discoveries in the tumor microenvironment have led to changes in the management of melanoma and it is rising up hopes, specially, to those in advanced stages. FDA approved seven new drugs from 2011 to 2014. They are: Vemurafenib, Dabrafenib and Trametinib, kinases inhibitors used for patients that have BRAFV600E mutation; Ipilimumab (anti-CTLA4), Pembrolizumab (anti-PD-1) and Nivolumab (anti-PD-1), monoclonal antibodies that stimulate the immune system; and Peginterferon alfa-2b, an anti-proliferative cytokine used as adjuvant therapy. In this article, we will review the molecular bases for these new metastatic melanoma therapeutic agents cited above and also analyze new molecular discoveries in melanoma study, as Cancer-Testis antigens (CT). They are capable of induce humoral and cellular immune responses in cancer patients and because of this immunogenicity and their restrict expression in normal tissues, they are considered an ideal candidate for vaccine development against cancer. Among CT antigens, NY-ESO-1 is the best characterized in terms of expression patterns and immunogenicity. It is expressed in 20-40% of all melanomas, more in metastatic lesions than in primary ones, and it is very heterogeneous inter and intratumoral. Breslow index is associate with NY-ESO-1 expression in primary cutaneous melanomas, but its relation to patient survival remains controversial.